A Novel Aluminum‐Based Metal‐Organic Framework with Uniform Micropores for Trace BTEX Adsorption. (9th February 2023) - Hu, Laigang; Wu, Wenhao; Gong, Li; Zhu, Hongxia; Jiang, Ling; Hu, Min; Lin, Daohui; Yang, Kun
Abstract: Metal‐organic frameworks (MOFs) are potential porous adsorbents for benzene, toluene, ethylbenzene and xylene (BTEX). A novel MOF, using low toxic aluminum (Al) as the metal, named as ZJU‐620(Al), with uniform micropore size of 8.37±0.73 Å and specific surface area of 1347 m 2 g −1, was synthesized. It is constructed by one‐dimensional rod‐shaped AlO6 clusters, formate ligands and 4, 4′, 4′′‐(2, 4, 6‐trimethylbenzene‐1, 3, 5‐triyl) tribenzoic ligands. ZJU‐620(Al) exhibits excellent chemical‐thermal stability and adsorption for trace BTEX, e.g ., benzene adsorption of 3.80 mmol g −1 at P / P 0 =0.01 and 298 K, which is the largest one reported. Using Grand Canonical Monte Carlo simulations and Single‐crystal X‐ray diffraction analyses, it was observed that the excellent adsorption could be attributed to the high affinity of BTEX molecules in ZJU‐620(Al) micropores because the kinetic diameters of BTEX are close up to the pore size of ZJU‐620(Al). Abstract : A novel Al‐based MOF is described with uniform micropore size of 8.37±0.73 Å and excellent chemical‐thermal stability for trace BTEX, e.g., benzene adsorption of 3.80 mmol g −1 at relative pressure ( P / P 0 )=0.01 and 298 K, which is the largest value reported.